2019
DOI: 10.1186/s40104-019-0387-9
|View full text |Cite
|
Sign up to set email alerts
|

Low-protein diets supplemented with casein hydrolysate favor the microbiota and enhance the mucosal humoral immunity in the colon of pigs

Abstract: Background High-protein diets can increase the colonic health risks. A moderate reduction of dietary crude-protein (CP) level can improve the colonic bacterial community and mucosal immunity of pigs. However, greatly reducing the dietary CP level, even supplemented with all amino acids (AAs), detrimentally affects the colonic health, which may be due to the lack of protein-derived peptides. Therefore, this study evaluated the effects of supplementation of casein hydrolysate (peptide source) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 47 publications
4
21
0
Order By: Relevance
“…Dietary supplementation of weaned and growing pigs with casein-derived peptides was also associated with an increase in butyrate production. 49,50 YBG, contrarily, decreased butyrate concentration. This is probably linked with the reduction of certain members of the microbiota due to YBG supplementation.…”
Section: Compoundmentioning
confidence: 84%
See 1 more Smart Citation
“…Dietary supplementation of weaned and growing pigs with casein-derived peptides was also associated with an increase in butyrate production. 49,50 YBG, contrarily, decreased butyrate concentration. This is probably linked with the reduction of certain members of the microbiota due to YBG supplementation.…”
Section: Compoundmentioning
confidence: 84%
“…The ability of 5kDaR to stimulate lactobacilli growth within a complex microbial community was in agreement with previous studies in which the ileal and colonic counts of this bacterial population were increased in weaned and growing pigs supplemented with casein-derived peptides. 49,50 An additional bacterial group that was measured in the batch fermentation assay was Prevotella spp. which is the predominant genus in weaned pigs.…”
Section: Compoundmentioning
confidence: 99%
“…As the main nitrogen source of the intestinal microbe, dietary protein has been proven to significantly change the bacterial community. Wang et al reported that low protein diets improved hindgut health by preventing the proliferation of pathogenic bacteria ( 22 ). A better digestible protein source also reduced the risk of colitis under the same protein level ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, protein or amino acid restriction and amino acid supplementation also changed the composition of intestinal microbiota. Wang et al. (2019) reported that low-protein diets with casein hydrolysate reduced the concentrations of putrescine, phenol, and indole compounds in the colonic digesta of pigs and the relative abundance of L. reuteri in the colon of pigs at the species level, when compared with diets added with free amino acids.…”
Section: Effects Of Dietary Protein/amino Acid Metabolism On Intestinal Microorganismsmentioning
confidence: 99%